IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERMUAHAN SWADAYA TAHUN 2016 (STUDI KASUS KOTA PEKANBARU) - Nuraida Mailasari; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The house is a basic need and has a function that is essential for human life. The house also as one of the main elements for the welfare of the people. To improve the welfare of the people the government implement a program to assist low-income communities (MBR) to obtain appropriate housing.One government program is a program BSPs issued by the Ministry PUPR under Regulation Ministry of Public Works and Public Housing No. 13 / PRT / M / 2016 on Governmental Housing Assistance stimulants. BSPs program will be implemented by the provincial government through the Department of Public Works in every province. Pekanbaru City North Tangkerang particularly sub-district is one of the program managers BSPs, North Tangkerang a result of the development of the Village area Tangkerang.The purpose of this study was to determine how the implementation of the Regulation of the Ministry of Public Works and Public Housing No. 13 / PRT / M / 2016 on Governmental Housing Assistance stimulants. This research was conducted using qualitative research method by using interview, observation and documentation by using key informants and results on the ground as a source of information.These results indicate that the BSPs Department of Housing, Settlement and Land Region of Riau Province as Committing Officer and the Department of Housing and Settlement Region Pekanbaru City as Technical team BSPs program has been implemented properly. The problems caused by less accurate data so that the receiver can register themselves every aspect of the program so much that did not pass the identification and verification, as well as recipients who refuse to accept the program because we are not able to do self-help, and the lack of building materials from material suppliers.Keywords: Implementation, District of North Tangkerang